Knowledge, Attitude, and Practice of Breast-Self Examination Among Female Students of Niger Delta University - Oboli, Deborah; Mkpae, Oluchi; Gbuchie, Monica Anurika; Gbuchie, Tonte (International Journal of Medical Students, 2025)
BACKGROUND: Cancer, characterized by uncontrollable cell division leading to tissue destruction, is a leading cause of death globally. Breast cancer, in particular, affects 2.1 million women annually and causes significant mortality, especially in less developed regions due to late detection and limited access to treatment. In Nigeria, the incidence rate of breast cancer is 33.6 per 100,000 women. Early detection through methods like breast self-examination (BSE) is crucial, particularly in developing countries where mammography may not be feasible. BSE is recommended due to its simplicity, privacy, and lack of cost, yet awareness and practice remain low. This study assesses the knowledge, attitude, and practice of BSE among female students at Niger Delta University to provide insights into the effectiveness of current awareness efforts. METHODS: A descriptive cross-sectional study was conducted over six weeks at Niger Delta University, Bayelsa State, Nigeria. A sample of 376 female undergraduates, aged 18-30 years, was selected using multistage sampling. Data was collected through semi-structured, self-administered questionnaires. Knowledge of BSE was assessed through a scoring system, and attitudes and practices were evaluated based on responses to various statements and self-reported practices. The data was analyzed using SPSS version 21, with knowledge scores categorized as poor (0-4), fair (5-7), or good (8-9). RESULTS: Of the respondents, 77.4% were single, and 60.9% had good knowledge of BSE, while 35.4% had fair knowledge, and 3.7% had poor knowledge. Attitude towards BSE was generally positive, with 72.6% agreeing that BSE is not time-consuming. The practice of BSE was reported by 64.4% of respondents, with 96.7% performing it at least monthly. Knowledge of BSE was notably higher among students from medical departments, and those with a family history of breast cancer. The study indicated that increased awareness and education have contributed to better knowledge and practice of BSE compared to past studies. CONCLUSION: The study highlights a significant level of awareness and positive attitude towards breast self-examination among female students at Niger Delta University. Despite the encouraging practice rates, there remains a need for continuous education and outreach to further improve the regular practice of BSE and enhance early detection of breast cancer.